Understanding the Montessori approach : early years education in practice - Isaacs, Barbara, 1949- (Routledge, Taylor & Francis Group, 2018)
Understanding the Montessori Approach is a much-needed source of information for those wishing to extend and consolidate their understanding of the Montessori Approach and how it is used in the teaching and learning of young children. The book will enable the reader to analyse the essential elements of this Approach to early childhood and and its relationship to quality early years practice. (Nakladatelská anotace)
Keywords: metoda Montessori; předškolní výchova; pedagogická praxe; vývoj dítěte; Montessori method of education; preschool education; practice teaching; child development; monografie; monographs